Effect of Feeding Rate on the Reduction of Total Volatile Solids and Organic Carbon during Combined Composting and Vermicomposting of Elephant Dung - Parajuli, Arun Prasad; Amatya, Iswar Man; Sharma, Ram Kumar (Journal of Advanced College of Engineering and Management, 2018)
One of the methods of treatment of animal waste to conserve our nature is vermicomposting in which waste-feeding rate is one of the important parameters to be considered. This paper is concerned with studying and analyzing the effect of feeding rate on the reduction of total volatile solid and total organic carbon during vermicomposting of elephant dung. The raw dung collected from the Central Zoo, Jawalakhel, Nepal was composted in a heap on the open ground after removal of inorganic substances by hand sorting and manually breaking of lumps. Composted dung only after two weeks was feed in the circular earthen flower pots having average diameter of 0.15 m and surface area of 0.017 m2 each with small holes at the bottom. The adult healthy Eiseniafetida with a stocking density of 1.6 kg-worm/m2 with feeding rates of 0.75, 1, 1.5 and 2kg-feed/kg worms/day in the batch basis were used in the separate sets for vermicomposting in moisture content of 70 to 80% at normal room condition in two cycles of eight weeks after two weeks of normal composting in a room. It was revealed from the experiment that the combined composting and vermicomposting system with feeding rate of 0.75 kg-feed/kg worms/day was more effective in reducing total volatile solids and total organic carbon content to 42.52% and 23.62% respectively after ten weeks.